2021
DOI: 10.1093/bbb/zbaa080
|View full text |Cite
|
Sign up to set email alerts
|

Development of an itraconazole resistance gene as a dominant selectable marker for transformation in Aspergillus oryzae and Aspergillus luchuensis

Abstract: There are only a few combinations of antifungal drugs with known resistance marker genes in the Aspergillus species; therefore, the transformation of their wild-type strains is limited. In this study, to develop the novel dominant selectable marker for itraconazole, a fungal cell membrane synthesis inhibitor, we focused on Aspergillus luchuensis cyp51A (Alcyp51A), which encodes a 14-α-sterol demethylase related to the steroid synthesis pathway. We found that the G52R mutation in AlCyp51A and the replacement of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The results indicated that a higher electric field intensity contributed to the uptake rate of these plasmids with relatively large sizes in M. circinelloides, consistent with the results reported in Aspergillus fumigatus . In addition, the transformation efficiency at resistance 200 Ω was 14–50 transformants per 10 7 spores, which was 2–8-folds higher than that of resistance 400 Ω (7–30 transformants per 10 7 spores).…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that a higher electric field intensity contributed to the uptake rate of these plasmids with relatively large sizes in M. circinelloides, consistent with the results reported in Aspergillus fumigatus . In addition, the transformation efficiency at resistance 200 Ω was 14–50 transformants per 10 7 spores, which was 2–8-folds higher than that of resistance 400 Ω (7–30 transformants per 10 7 spores).…”
Section: Resultsmentioning
confidence: 99%
“…In-depth investigations portrayed a higher microsomal P450 levels leading to increased ergosterol synthesis in the resistance strain and was responsible for both azole and amphotericin B resistance [ 44 ]. These findings indicate that the cross-resistance to such two triazoles was caused by elevated P450 levels [ 45 ]. In the small number of clinical isolates with 14 α -demethylase overexpression, this phenomenon was only seen in C. glabrata, and the possibility that other resistance mechanisms are active in the same strain all suggests that increased expression of the target enzyme ends up playing just a minor role in clinical azole resistance [ 46 ].…”
Section: Mechanism Antifungal Drug Resistancementioning
confidence: 99%